More Similarities Than Differences? An Exploratory Analysis Comparing the Sexual Complaints, Sexual Experiences, and Genitourinary Health of Older Sexual Minority and Sexual Majority Adults. Issue 3 (1st March 2019) - Obedin-Maliver, Juno; Lisha, Nadra; Breyer, Benjamin N.; Subak, Leslee L.; Huang, Alison J.
Abstract: Background: Little is known about sexual problems and genitourinary health of older sexual minority adults, who comprise up to 4% of the adult population but may differ in experiences of genitourinary aging, given known health disparities and behavior differences. Aim: To examine and compare genitourinary and sexual complaints among older sexual minority and sexual majority adults. Methods: We analyzed data from the 2010–2011 National Social Life, Health, and Aging Project (NSHAP), a nationally representative sample of older community-dwelling U.S. adults. Sexual minority men were defined as those who have sex with men or with both women and men. Sexual minority women were those who have sex with women or with both women and men. Descriptive statistics, weighted frequencies, and the chi-square test were used to compare outcomes by sexual orientation group and gender. Main Outcome Measures: Structured questionnaires examined sexual activity, practices, and genitourinary problems such as erectile dysfunction, insufficient vaginal lubrication, and urinary incontinence (UI). Results: Of 2, 813 participants (median age 69.6 years), 4.2% were sexual minorities (5.3% of men, 3.5% of women). Among men, sexual minorities were more likely to report UI (35.6% vs 21.8%; P  = .029), but otherwise the 2 groups had similar prevalences of other urinary symptoms, importance of sexual activity, sexual practices, sexual activity within the last 3 months, and erectile difficulty ( P > .10 for all). Among women, sexual minorities were more likely to report receiving oral sex (42.5% vs. 21.2%; P  = .004), but otherwise the 2 groups had similar prevalences of UI, other urinary symptoms, importance of sexual activity, sexual activity within the last 3 months, and difficulty with lubrication ( P > .10 for all). Clinical Implications: Sexual activity and sexual problems may be as common among older sexual minority adults as in their sexual majority counterparts, whereas UI may be more common in sexual minority men compared with sexual majority men. Therefore, clinicians should employ culturally-relevant health screening, diagnosis, and treatment to ensure reaching all adults regardless of sexual orientation. Strengths & Limitations: Strengths include a national population-based sample of older adults that describes sexual and genitourinary health. Statistical power was limited by the small numbers of sexual minority individuals. Conclusion: Here we provide new evidence that older sexual minority men may experience UI more often than sexual majority men, and that sexual practices may differ between sexual minority and majority women, but frequency of sexual problems is similar. Given the challenges faced by sexual minority individuals in accessing equitable health care, clinicians must ensure that diagnosis and treatment are relevant to people of all sexual orientations.